Can you forgive? It depends on how happy you are. Issue 2 (23rd December 2014) - Jiang, Feng; Yue, Xiaodong; Lu, Su; Yu, Guangtao
<x xml:space="preserve">Abstract</x> This paper examined how individual group status and happiness influence forgiveness. In Study 1, happiness was treated as a trait difference: highly happy people, compared with very unhappy people, were found to be more willing to forgive murderers. More important, an interaction effect between happiness and group status on forgiveness was found, that is, highly happy people tended to be more forgiving when either ingroup or outgroup members were killed; unhappy people, however, tended to be less forgiving about murder when ingroup rather than outgroup members were killed. In Study 2, happiness was treated as an emotional state difference: happiness, rather than sadness, was found to bring greater forgiveness. Moreover, consistent with the interaction effect displayed in Study 1, happy participants tended to forgive more when ingroup or outgroup members were hurt; sad participants tended to forgive less when ingroup members rather than outgroup members were hurt. Implications for connections between happiness, group membership, and forgiveness are discussed.